Parametric Studies of Shape Memory Alloy Hybrid Composite Laminates Under Low-Velocity Impact. (20th April 2016) - Lin, Y.-C.; Chen, Y.-L.; Chen, H.-W.
Abstract : In the paper, the influence of shape memory alloy (SMA) by varying the parameters such as volume fraction, orientation, and temperature on the hybrid-SMA composite laminate subjected to low-velocity impact is studied. A theoretical model for the composite laminated plate bonded with SMA reinforced layers is presented. The constitutive relation of the SMA layer is obtained by using the method of micromechanics. The governing relations obtained can be used for theoretical predications of thermomechanical properties of SMA plies in this paper. The analytical expressions for the hybrid SMA composite plate are derived based on Tanaka's constitutive equation and linear phase transformation kinetics presented by Liang and Rogers. The laminated plate theory, first-order shear deformation theory and minimal potential energy principle is utilized to solve the governing equations of the hybrid composite plate and calculate the absorbed energies including tensile, shear and bending. An orthogonal array and analysis of variance is employed to investigate the influence of the mentioned parameters on the energy absorption of the hybrid laminated plate. The results showed that the effects of the phase transformation temperature are more significant than the effects of the volume fraction and orientation of SMA on structural energy absorption.